2016
DOI: 10.1002/jcla.22099
|View full text |Cite
|
Sign up to set email alerts
|

National continuous surveys on internal quality control for HbA1c in 306 clinical laboratories of China from 2012 to 2016: Continual improvement

Abstract: The imprecision performance of HbA1c tests has been improved in these 5 years with the change in IQC practice, but it is still disappointing in China. Therefore, laboratories should actively find existing problems and take action to promote performance of HbA1c measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There are many ways to set analytical quality specifications in laboratory medicine. The Stockholm Conference held from April One QC run more than 2 days One QC run every 1-2 days More than one QC run every day [24][25][26]1999, achieved a global consensus on the setting of analytical quality specifications in laboratory medicine and advocated for the ubiquitous application of a hierarchical structure of approaches (the hierarchy has five levels). 13,14 After 15 years, the Organizers and whereas the 1/3TEa and 1/4TEa derived from CLIA'88 are model 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways to set analytical quality specifications in laboratory medicine. The Stockholm Conference held from April One QC run more than 2 days One QC run every 1-2 days More than one QC run every day [24][25][26]1999, achieved a global consensus on the setting of analytical quality specifications in laboratory medicine and advocated for the ubiquitous application of a hierarchical structure of approaches (the hierarchy has five levels). 13,14 After 15 years, the Organizers and whereas the 1/3TEa and 1/4TEa derived from CLIA'88 are model 3.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation on hemoglobin A1c has shown that CVs were influenced by vendors of QC materials. 24 It is a good beginning and a meaningful thing for NCCL in China to collect the IQC data from EQA participants using an additional part of EQA network platform and conducting some further statistical analysis although there were many limitations that existed in this national continual survey on IQC practice for cardiac biomarkers. However, we can conclude that the measurement precision of laboratories in China has yet to be improved, especially for some analytes, such as HCY.…”
Section: Discussionmentioning
confidence: 99%
“…This method involves the separation based on contrasting electric charge. 403 In this approach, the mechanism of analyte retention is based on the principle of electrostatic attraction between the sample and the stationary phase functional groups (FGs), having opposite charges. IEC is classified into two types: cationexchange and anion-exchange chromatography.…”
Section: Peptide Fractionation Methodsmentioning
confidence: 99%
“…404 These functional groups are most commonly supported in resins made up of silica and synthetic polymers, however, some inorganic materials are sometimes used. 403 In the IEC method, peptide elution is performed using a mobile phase with higher ionic strength, to ensure peptide partition into the liquid phase. SCX along with a salt gradient/plug is a routinely used proteomics technique.…”
Section: Peptide Fractionation Methodsmentioning
confidence: 99%
See 1 more Smart Citation